THE STATUS AND ROLE OF THE CORPORALITY AT ≪EARLY≫ C. MARX AND IN E. HUSSERL'S PHENOMENOLOGY - I. V. Kuzin (Дискурс, 2016)
This article represents interpretation and development of phenomenological approach of E. Husserl to a corporality problem with the aim to determine opportunities of comparison of this approach with K. Marx's provisions in the work «Economic and philosophical manuscripts of 1844». It is shown in research that Marx also has a subject of corporality (concreteness) as significant in disclosure of human nature. During the made analysis it becomes clear that between philosophical positions of these different thinkers there is a number of indirect (meaning) coincidence which identification does more clear relevance of a corporality problem.